1997
DOI: 10.1099/00221287-143-11-3607
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and protective activity of a monoclonal antibody against a capsular epitope shared by Streptococcus suis serotypes 1, 2 and 1/2

Abstract: A monoclonal antibody (mAb 23) was produced using BALBIc mice immunized with whole cells of Streptococcus suis serotype 2 reference strain S735. Screening by dot-ELISA showed that mAb 23, of isotype IgG2b, reacted only with reference strains and field isolates of 5. suis serotypes 1,2 and 1/2. The recognized epitope was demonstrated to be polysaccharide in nature by periodate oxidation, and located in the capsule, since mAb 23 reacted with purified capsular material by immunoblotting and was able to stabilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 43 publications
3
42
2
Order By: Relevance
“…To our knowledge, the capsule of S. suis serotype 2 is the first critical virulence factor described so far for this bacterium. (Charland et al, 1997). Other factors, such as extracellular or cellwall-associated proteins, are probably required for successful establishment of the bacteria in the host.…”
Section: Influence Of Defective Capsular Expression On Virulence and mentioning
confidence: 99%
“…To our knowledge, the capsule of S. suis serotype 2 is the first critical virulence factor described so far for this bacterium. (Charland et al, 1997). Other factors, such as extracellular or cellwall-associated proteins, are probably required for successful establishment of the bacteria in the host.…”
Section: Influence Of Defective Capsular Expression On Virulence and mentioning
confidence: 99%
“…These vaccines were named "glycoconjugate vaccines." Since it has been reported that anti-CPS antibodies, if produced, have a high protective potential against infection caused by S. suis (22,23), an interesting strategy for the development of an S. suis type 2 vaccine would be the use of a glycoconjugate vaccine made of CPS coupled to an immunogenic carrier protein, such as tetanus toxoid (TT), diphtheria toxoid, cross-reactive material 197 (CRM 197 ), or many more (24). As a matter of fact, glycoconjugate vaccines are very successful in the fight against encapsulated human pathogens such as Haemophilus influenzae (Hiberix), Neisseria meningitidis (MenACWY), and Streptococcus pneumoniae (PCV13) (20).…”
mentioning
confidence: 99%
“…Antigen A is probably the group antigen of S. iniae, because it is acid-extractable and has carbohydrate nature (Pier et al, 1978;Bachrach et al, 2001). It is known that specific antibodies stabilize bacterial capsules (Bayer and Thurow, 1977;Charland et al, 1997;Yoshida et al, 1997;Vanrobaeys et al, 1999 (Fig. 2c).…”
Section: Discussionmentioning
confidence: 99%
“…Samples for transmission electron microscopy were prepared as described by Charland et al (1997) with some modifications. Briefly, one loopful of bacterial colonies grown on TH agar was suspended in 2 mL PBS, added with 40 µL of rabbit anti-NUF38 or anti-NUF631 serum and incubated for 3 h at 4°C.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%